Membina Kemampuan Kepala Sekolah dalam Melakukan Evaluasi dan Pelaporan Pelaksanaan Program Kegiatan Sekolah melalui Supervisi Manajerial di Wilayah Kepengawasan Gugus Sekolah 03 Kecamatan Prajuritkulon dan Gugus Sekolah 01 Kecamatan Kranggan Kota Mojokerto - Sunarijah (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2018)
In this global era, the ability of schools to change depends on their capacity to learn ... Principals, for example, must comply with various system requirements and manage routine administrative tasks. The principal is required to be able to evaluate and report on the implementation of school activities. The purpose of this study are: Describe the ability of the principal in evaluating and reporting the implementation of school activity programs in the field of Work Programs, Regulations and Decisions, Guidance, Other Administration through managerial supervision in School Cluster Monitoring Areas 03 Prentarakulon District and School Clusters 01 Kranggan District Mojokerto City . This research uses action research as many as two cycles. Each cycle consists of one meeting, each meeting consisting of four stages: design, activities and reflection and revision observations. The target of this research is the Principal in the School Cluster Monitoring Area 03 of the Prentarakulon and School Cluster 01 District of Kranggan, Mojokerto City with 12 people. Data obtained in the form of managerial supervision results which include: Work Programs, Regulations and Decisions, Guidance, Other Administration. The success of the learning process in cycle II shows that the cycle can be stopped because it has met the target of> 80%. This is evident from the average increase in the performance of principals from 72.70% in the initial conditions, increasing to 78.92% in the first cycle and increasing to 87.81% in the second cycle. The conclusions of this research are: 1) The principal can evaluate and report on the implementation of the school activity program in the Field of Work Program through managerial supervision. 2) Principals can evaluate and report on the implementation of school activities in the field of Regulations and Decisions through managerial supervision. 3) The principal can evaluate and report on the implementation of school activities in the field of guidance through managerial supervision. 4) The school principal can evaluate and report on the implementation of other administrative activities in the school administration program through managerial supervision